Correlations Between Phenolic Composition and Perceived Astringency of Wines - Kyeong-Ok Choi; Dong Hoon Lee; Seo Jun Park; Dongjun Im; Youn Young Hur (Applied Sciences, 2020)
The astringent sensation of wines is attributable to the composition and concentration of phenolic compounds. However, in many cases, experimental results have shown a gap in relation to sensory astringency. The aim of the present study was to evaluate the relationships between the experimental evidence of astringent attributes and perceived astringency. To this end, the concentrations of phenolic compounds, namely, the total phenolic content (TPC), the polymeric tannin content (PTC), the proanthocyanidin content (PAC) and the total anthocyanin content (TAC), in wines made from a variety of grape breeding lines were estimated and their relationships to perceived astringency were evaluated. The TPC and the PTC showed strong positive correlations with perceived astringency. In contrast, the PAC showed a moderate correlation with perceived astringency, which was lower than that shown by the PTC despite their similar phenolic compositions. Unlike the other attributes, the TAC showed a weak correlation with perceived astringency. We concluded that the TPC and the PTC showed good correlations with perceived astringency and could be used as an index for predicting the astringency of wines.